2017
DOI: 10.5430/jnep.v8n4p28
|View full text |Cite
|
Sign up to set email alerts
|

The effects of technology on stress and coping strategies in nurse educators

Abstract: The purpose of this study was to investigate the relationships among the independent variables of age, gender, years of experience as a nurse educator, and previous technology training, and the dependent variables of feeling compelled to respond to students after hours, level of stress experienced by nurse educators with technology (in general), and level of stress experienced by nurse educators with technology in the classroom/clinical setting. The researcher also investigated the coping strategies demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…While most students reported positive experiences using VBAs, technical issues posed a barrier to embracing this new approach to learning. This is consistent with other studies that found nursing students and nurse educators often struggling with emerging technologies [17,18]. Even though YouSeeU has a sync slides function for group work, the group oral presentation that required synchronization was reported as one of the most challenging tasks, as group members had to coordinate their different time zones and work schedules.…”
Section: Discussionsupporting
confidence: 88%
“…While most students reported positive experiences using VBAs, technical issues posed a barrier to embracing this new approach to learning. This is consistent with other studies that found nursing students and nurse educators often struggling with emerging technologies [17,18]. Even though YouSeeU has a sync slides function for group work, the group oral presentation that required synchronization was reported as one of the most challenging tasks, as group members had to coordinate their different time zones and work schedules.…”
Section: Discussionsupporting
confidence: 88%